CHANGES IN VASCULAR-RESISTANCE DURING CAROTID OCCLUSION IN NORMAL AND BARORECEPTOR-DENERVATED RATS - Machado, B. H.; Bonagamba, LGH; Castania, J. A.; Menani, José Vanderlei [UNESP] (Amer Heart Assoc, 1992)
In the present study, we investigated changes in mesenteric, renal, and hindquarter vascular resistance during the pressor response produced by bilateral carotid occlusion (BCO) in conscious, freely moving normal and denervated (aortic, carotid, or both) rats. BCO was performed using special previously implanted cuffs. In control normal rats, the increase in mean arterial pressure (MAP) during early and late responses (37 +/- 4 and 21 +/- 2 mm Hg, respectively) was related to increased renal (125 +/- 12% and 45 +/- 10%) and mesenteric (38 +/- 13% and 41 +/- 5%) but not hindquarter (14 +/- 4% and 8 +/- 7%) vascular resistance. In aortic-denervated rats, the greater MAP increase in early and late responses (57 +/- 4 and 44 +/- 4 mm Hg, respectively) compared with normal rats was related to a marked increase in hindquarter (137 +/- 26% and 106 +/- 26%) and mesenteric (104 +/- 14% and 66 +/- 9%) vascular resistance. In carotid-denervated rats, MAP increase and change in vascular resistance were similar to those values observed in control rats. Sinoaortic-denervated rats showed a greater MAP increase (34 +/- 4 mm Hg) during late response and a reduced increase in renal vascular resistance (46 +/- 6%) during early response. The present results show that 1) the pressor response to BCO in normal rats is associated with an increase in renal and mesenteric vascular resistance, 2) the aortic baroreceptors buffer the increase in mesenteric and especially hindquarter vascular resistance during BCO, and 3) the reduced pressor response in late response is probably related to a reduced increase in renal vascular resistance during this component compared with the early response.
Keywords: VASCULAR RESISTANCE; CAROTID ARTERY; BARORECEPTORS; ISCHEMIA